The development of a school uniform for preschool children - Callos, Ma. Gina R.; Dizon, Angelita Mendoza (1993.)
In a desire to develop a fairly acceptable uniform for the pre-schoolers, a study of the present school uniforms of five (5) selected pre-schools in Diliman, Quezon City was conducted. Seventy (70) respondents, composed of fifty-five (55) parents and fifteen (15) teachers, were randomly chosen. They were given questionnaires to evaluate the present school uniform. The results of the evaluation showed that the majority of the respondents were not satisfied with the present pre-school uniform since they were inadequate as far as comfort, safety, self-help, allowance for growth, easy care, appearance, and protection were concerned. Based on the results of this evaluation and the review of related literature, a set of criteria was developed to serve as a guide in conceptualizing a new pre-school uniform. The design consisted of a loose dress, above the knee in length, with kimono sleeves front buttons, snap opening and a bow, and patch pockets for the girls and a polo and pants for the boys. The polo has a convertible collar, front opening with set-in sleeve while the pants has zipper front opening with slant patch pocket. A prototype of the new design was constructed and tested for acceptability by fitting it to child model and was asked to move around and play, while the researcher and parents were observing the model. The prototype design was easy to assemble with low to moderate cost.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Preschool children -- Clothing; Children's clothing